Identification, physical map location and sequence of the denV gene from bacteriophage T4. - Valerie, K (1984)
The denV gene from bacteriophage T4, which codes for endonuclease V, a small DNA repair enzyme, has been cloned and identified by an approach combining DNA sequencing and genetics, independent of the phenotypic effect of the cloned gene. Appropriate DenV+ and DenV- deletion mutants were mapped physically to define precisely a region encompassing the denV gene. This region was sequenced in order to identify a protein-coding sequence of the correct size for the denV gene (400-500 bp). Finally, identification was confirmed by sequencing the corresponding fragments cloned from four genetically and phenotypically well-characterized denV mutants. The denV gene is located at 64 kb on the T4 genome, adjacent to the ipII gene, and codes for a basic protein of 138 amino acids with a deduced molecular weight of 16,078.